LIFE CYCLE ASSESSMENT OF MICRO SMALL AND MEDIUM ENTERPRISES (MSMES) FOR BILIH FISH PRODUCTS IN SOLOK REGENCY, WEST SUMATERA - Fajri, Wilda Wirdatul; Yani, Mohamad; Suprihatin (Jurnal Teknologi Industri Pertanian, 2025)
Bilih fish is a freshwater fish endemic at Lake Singkarak, West Sumatra, and can be processed to increase this added value. The development of the fishery industry provides significant economic benefits and contributes to environmental impacts. This research aimed to assess the life cycle of crispy balado bilih fish products from Tujuh Muaro (TM) micro-enterprise and regular fried bilih fish products from Tabiang Biduak Lestari (TB) microenterprise using the Life Cycle Assessment (LCA) method. The scope of this study is cradle-to-grave, covering bilih fish fishing, transportation of raw materials and packaging, production processes, and distribution, with a functional unit of 100 g/package of bilih fish product. The impact analysis was conducted using SimaPro software, based on the CML 2001-IA baseline method for impact categories, including Global Warming Potential (GWP), Acidification (AP), and Eutrophication (EP). The micro-enterprises generated GWP impacts with normalised values of TM 6.51E-14 and TB 1.28E-14, AP 3.86E-14 and 1.19E-14, EP 5.81E-13, and 7.96E-14 person equivalents, respectively. Improvement scenarios at the production unit were carried out by substituting frying methods to reduce cooking oil usage, which lowered impacts with GWP reductions of 84.85% (TM) and 51.93% (TB), and AP reductions of 52.63% and 17.86%, EP reductions of 96.08% and 81.35%. In the transportation unit, selecting packaging suppliers closer to TM reduced impacts by 94.22% for GWP, 94.23% for AP, and 94.25% for EP. Utilising waste oil as biodiesel further reduced GWP impacts by 90.48% (TM) and 82.87% (TB), AP by 97.50%, and 94.78%, EP by 98.80%, and 98.14% respectively. Keywords: bilih fish, environmental impact, LCA